Electric Mobility in India : Accelerating Implementation - World Bank (World Bank, Washington, DC, 2021)
Governments, automotive manufacturers, energy companies, charging infrastructure operators, mobility service providers, technology providers and aggregators across the globe are preparing themselves for a rapid transition from conventional internal combustion engine (ICE) vehicles to electric mobility. Increasing from the current global sales of 2.1 million units in 2019, electric vehicles are expected to account for nearly 57 percent of all vehicle sales and over 30 percent of all vehicle fleet by 2040. International experience indicates that the key factors responsible for driving this transition are a) conducive policy and regulatory support across the electric mobility value chain, b) technological advancements (new and improved battery chemistries, automation in retail electricity business) and c) increased customer preference for green mobility options (influenced by rising fuel prices and concerns regarding local air pollution, climate change). An analysis was undertaken by the World Bank to review the development of e-mobility in India, identify remaining challenges and mitigation measures to support India’s electric mobility vision. This report presents the findings of the analysis and lays out a set of recommendations for consideration by different stakeholders.